Bertrand's paradox and the principle of indifference - Shackel, Nicholas, 1955- (New York, NY : Routledge, 2024)
"Events between which we have no epistemic reason to discriminate have equal epistemic probabilities. Bertrand's chord paradox, however, appears to show this to be false, and thereby poses a general threat to probabilities for continuum sized state spaces. Articulating the nature of such spaces involves some deep mathematics and that is perhaps why the recent literature on Bertrand's Paradox has been almost entirely from mathematicians and physicists, who have often deployed elegant mathematics of considerable sophistication. At the same time, the philosophy of probability has been left out. In particular, left out entirely are the philosophical ground of the principle of indifference, the nature of the principle itself, the stringent constraint this places on the mathematical representation of the principle needed for its application to continuum sized event spaces, and what these entail for rigour in developing the paradox itself. This book puts the philosophy and its entailments back in and in so doing casts a new light on the paradox, giving original analyses of the paradox, its possible solutions, the source of the paradox, the philosophical errors we make in attempting to solve it and what the paradox proves for the philosophy of probability. The book finishes with the author's proposed solution-a solution in the spirit of Bertrand's, indeed-in which an epistemic principle more general than the principle of indifference offers a principled restriction of the domain of the principle of indifference. Bertrand's Paradox and the Principle of Indifference will appeal to scholars and advanced students working in the philosophy of mathematics, epistemology, philosophy of science, probability theory, and mathematical physics"--
The principle of indifference -- The principle of indifference for sets -- Bertrand's paradoxes -- The threat to the principle and four kinds of solution -- The distinction strategy -- The well-posing strategy -- The irrelevance strategy -- The maximum entropy principle -- The universal average -- Meta-indifference -- Permissivism -- Uniqueness a criterion of identity -- Symmetry : the forlorn hope -- Unearthing the root -- Bertrand's temptations -- Rational strength.
Keywords: Bertrand, Joseph, -- 1822-1900.; Probabilities; Paradox; Logic, Symbolic and mathematical; PHILOSOPHY / Epistemology; SCIENCE / Philosophy & Social Aspects